ABUNDANCE AND COMPOSITION OF PHYTOPLANKTON IN MILKFISH (Chanos chanos) TRADITIONAL PONDS IN SIDOARJO, EAST JAVA - Anjasmara, Aang Setyawan; Lestariaji, Chandika; Rizal, Daisy Rahma; Agriandini, Maulina; Syarifudin, Andri (Universitas Mataram, 2025)
Aquatic environmental management is needed to carry out aquaculture in traditional ponds.The purpose of this study was to reveal and explain the composition of phytoplankton intraditional milkfish (Chanos chanos) ponds in Sidoarjo, East Java. The study was conducted inAugust - September 2024 in traditional ponds in Sidoarjo, East Java. The results showed thatthe plankton community structure found 37 phytoplankton genera in 3 divisions Chrysophyta,Chlorophyta, and Cyanophyta. The values ranged from 2179-27620 Ind / ml which includedmesotrophic waters, the diversity index ranged from 1.92 - 2.72 in the moderate category, andthe dominance index ranged from 0.27 - 0.45 which was classified as low. Air qualityparameters include temperature 30-31,8oC, brightness 38-41,5 cm, pH 9, dissolved oxygen6,87-8,4 mg/L, salinity 7-9 ppt, alkalinity 141-169 ppm, nitrate 0,87-2,35 mg/L, andorthophosphate 0,02-0,089 mg/L. As aquaculture in traditional ponds, air and soil qualitymanagement should be carried out during the preparation and maintenance of milkfish (Chanoschanos) ponds so that aquaculture management is maintained